2012
DOI: 10.1039/c2cc33232a
|View full text |Cite
|
Sign up to set email alerts
|

Mild ketone formation via Ni-catalyzed reductive coupling of unactivated alkyl halides with acid anhydrides

Abstract: Ni-catalyzed ketone formation through mild reductive coupling of a diverse set of unactivated alkyl bromides and iodides with particularly aryl acid anhydrides was successfully developed using zinc as the terminal reductant. These conditions also allow direct coupling of alkyl iodides with aryl acids in the presence of Boc(2)O and MgCl(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(53 citation statements)
references
References 54 publications
2
49
0
2
Order By: Relevance
“…The coupling protocols are suited for primary and secondary alkyl halides with acid derivatives, including acid chlorides, anhydrides, and in situ activated acids in the presence of Boc 2 O and MgCl 2 [63][64][65][66][67][68]. Although initial development was centered on primary and secondary alkyl iodides, finely tuning the reaction parameters satisfied alkyl bromides.…”
Section: Ketone Synthesismentioning
confidence: 99%
“…The coupling protocols are suited for primary and secondary alkyl halides with acid derivatives, including acid chlorides, anhydrides, and in situ activated acids in the presence of Boc 2 O and MgCl 2 [63][64][65][66][67][68]. Although initial development was centered on primary and secondary alkyl iodides, finely tuning the reaction parameters satisfied alkyl bromides.…”
Section: Ketone Synthesismentioning
confidence: 99%
“…16 Finally, although several mechanisms had been proposed in the literature for these reactions by ourselves and others, recent investigations have led to a revised mechanism. We proposed a connection between the cross-electrophile coupling of aryl halides with alkyl halides based upon mechanistic studies of isolated acylnickel intermediates 17 and subsequent work by Gong 12 suggested that the mechanism is nearly identical to the one we proposed for the coupling of aryl halides with alkyl halides. 18 …”
Section: Discussionmentioning
confidence: 89%
“…For example, Gong reported modified conditions that enable coupling with anhydrides 12 as well as the use of tertiary alkyl halides, 13 aryl acid chlorides, 14 and methyl p -toluenesulfonate ester. 15 It is also important to note that one-pot protocols for the generation and coupling of acid chlorides 14 and anhyrides 13 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Pleasingly, the Lewis acid activation of more challenging electron-rich aromatic andh eteroaromatic carboxylic anhydrides allowedf or the generation of the corresponding carbonyl radicals and the efficient synthesis of products 3d, 3e and 3g-j. [11,12] As al imitation, hydrocinnamic anhydride was found to be unreactive under these conditions. With respectt ot he olefin reactionp artner (Table 3), the protocol could be applied to differently substituted N-phenylacrylamides, obtaining products 3k and 3l in excellent yields.…”
mentioning
confidence: 99%